Diachronous Growth of the Northern Tibetan Plateau Derived From Flexural Modeling. Issue 8 (28th April 2021) - Wang, Lin; Cheng, Feng; Zuza, Andrew V.; Jolivet, Marc; Liu, Yiduo; Guo, Zhaojie; Li, Xiangzhong; Zhang, Changhao
Abstract: The early Cenozoic topography of the northern Tibetan plateau remains enigmatic because of the paucity of independent paleoelevation constraints. Long‐held views of northward propagating deformation imply a low Paleogene elevation, but this prediction is speculative. We apply flexural modeling to reconstructed Paleogene isopach data obtained from the Qaidam basin, which requires a larger topographic load in the Qilian Shan and a smaller load in the Eastern Kunlun Shan. Incorporating knowledge of proto‐Paratethys marine incursions in the Paleogene Qaidam basin, we infer a topographically low (0.4–1.0 km) Eastern Kunlun Shan and a higher (0.4–1.5 km) Qilian Shan during the Paleogene. This implied paleo‐relief contrasts with previous predictions and suggests more recently, Neogene surface uplift in the Eastern Kunlun Shan has been more significant than in Qilian Shan, highlighting diachronous growth of the northern Tibetan plateau. The low‐moderate paleoelevation implies a warmer and more humid climate in Northern Tibet during the Paleogene. Plain Language Summary: The Tibetan plateau is Earth's highest and largest plateau and has a protracted growth history closely related to Cenozoic convergence between India and Asia. Resolving its paleoelevation in the early Cenozoic is instructive to understand its growth history and Asian climate changes. Although paleoaltimetry studies have provided critical constraints for the southern Tibetan plateau during Paleogene, the paleoelevation of the northern Tibet remains enigmatic. The largest basin in the plateau is the Qaidam Basin, surrounded by high elevation thrust belts. We conducted flexural modeling of early Cenozoic strata from the Qaidam basin, which suggests higher topography in the north (0.4–1.5 km) and lower topography (0.4–1.0 km) in the south. This unique topographic relief in the northern Tibetan plateau suggests that very significant surface uplift (3–4 km) occurred along the southern margin of Qaidam basin in the late Cenozoic. These results of early topographic relief in northern Tibet support hypotheses of a Paleogene warmer and more humid climate in North Tibet. This study provides a new approach that provides an independent constraint on the Paleogene paleoelevation of northern Tibet, contributing to our understanding of the growth of the Tibetan plateau and Asian paleoclimate. Key Points: Flexural modeling shows topographic loads generated by Eastern Kunlun Shan and Qilian Shan account for the subsidence of the Qaidam basin We infer a low (0.4–1.0 km) Eastern Kunlun Shan and a moderate (0.4–1.5 km) Qilian Shan during the Paleogene Neogene surface uplift was more pronounced in the Eastern Kunlun Shan compared with Qilian Shan